Tracing teachers' classroom management concerns: a case study on four TESL student teachers / Diane Sima Anak Douglas Telajan - Douglas Telajan, Diane Sima (2009)
This study investigates the use of reflective journals among UiTM TESL studentteachers during their 10 weeks of formal teaching practise. This study focuses on the use of reflective journals in tracing the classroom management concerns of the student-teachers during their formal teaching practise. In this study, teachers' classroom management is categorized into three categories that are establishing physical and psychological environment, and monitoring students' behaviour and learning progress. Aside from that, this study also attempts to find out the studentteachers' perceptions on the use of the reflective journals. The data of this research is obtained from document analyses from the student-teachers' diaries and interviews done with the student-teachers. The interviews were done on two of the four research participants due to logistic reasons. From the document analysis of the student-teachers' diaries, it is found that reflective journals provide evidence of the student-teachers' concerns in classroom management especially in terms of their class' psychological environment and how they are to monitor their students' behaviour and learning progress. Moreover, based on the interviews done, it is essential to note that both participants believe that reflective journal writing would be beneficial if the teachers know how and what to reflect on. The results of this study also show that the UiTM TESL student-teachers have a positive attitude towards the use of reflective journals during their formal teaching training. It is also found that reflective journals are beneficial in helping the student-teachers improve their classroom management concerns by encouraging them to become more critical in their thinking. The findings from the study can be taken as examples for student-teachers in the future on what and how to go about writing their reflective journal. Aside from that, this study is beneficial for future student teachers in exposing them the various categories of classroom management that they need to keep in mind in the near future. Moreover, the findings that have been obtained from this study is helpful in giving insights to student-teachers that reflective journals can be used as a very useful learning tool for them. However, it is suggested that future research should focus on investigating the quality of reflection by student-teachers. It is also recommended to future researchers to include observation as one of the research instrument while interviews should be carried out on the student-teachers' supervisor and mentor in order to obtain information on their opinion regarding the observations they have done on the student-teachers.